2007
DOI: 10.1007/s11270-007-9340-1
|View full text |Cite
|
Sign up to set email alerts
|

Urban Influences on Stream Chemistry and Biology in the Big Brushy Creek Watershed, South Carolina

Abstract: Naturally high total dissolved solids and upstream agricultural runoff often mask the influence of urban land cover on stream chemistry and biology. We examined the influence of headwater urbanization on the water chemistry, microbiology, and fish communities of the Big Brushy Creek watershed, a 96 km 2 drainage basin in the piedmont of South Carolina, USA. Concentrations of most major anions and cations (especially nitrate, sulfate, chloride, sodium, potassium, and calcium) were highest in the urban headwater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
22
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 60 publications
7
22
0
Order By: Relevance
“…Our data supports the findings of other authors who reported significantly higher nitrate or orthophosphate in effluent impacted streams (e.g. Hoare 1984; Lewis et al 2007;Wahl et al 1997;Wernick et al 1998). Permitted effluent discharge for three of our treatment plants were available and these ranged from 0.75 MGD at Turkey, 4 MGD at Still and 8 MGD at Carter.…”
Section: Watersheds With Mixed Land Covers: Effect On Stream Solute Csupporting
confidence: 91%
See 3 more Smart Citations
“…Our data supports the findings of other authors who reported significantly higher nitrate or orthophosphate in effluent impacted streams (e.g. Hoare 1984; Lewis et al 2007;Wahl et al 1997;Wernick et al 1998). Permitted effluent discharge for three of our treatment plants were available and these ranged from 0.75 MGD at Turkey, 4 MGD at Still and 8 MGD at Carter.…”
Section: Watersheds With Mixed Land Covers: Effect On Stream Solute Csupporting
confidence: 91%
“…Our nitrate concentrations in treated sewage effluent were similar to and our phosphate concentrations High flow=black circles and Low flow=white circles. Inset diagram depicts the observed (x-axis) and predicted (y-axis) orthophosphate using high and low flow as independent variables much higher (Table 4) than those reported by Lewis et al (2007). Our data supports the findings of other authors who reported significantly higher nitrate or orthophosphate in effluent impacted streams (e.g.…”
Section: Watersheds With Mixed Land Covers: Effect On Stream Solute Csupporting
confidence: 89%
See 2 more Smart Citations
“…The majority of reported studies have been designed around specific questions such as the effects of urbanization on spring, stream, or ground-water quality, where sampling design is carefully developed to assess those features (Al-Kharabsheh 1999;Graniel et al 1999;Vidal and Melgar 2000;Jeong 2001;AlKharabsheh and Ta'any 2003;Khazaei et al 2004;Brilly et al 2006;Rose 2007;Peters 2009;Ma et al 2009;Aitkenhead-Peterson et al 2011). Point source pollution has traditionally been the target of most water-quality studies, not only because such investigations are usually easier to design and complete, but because point source contaminants have been the predominant issue in many parts of the world (Daniel et al 2002;Keraita et al 2003;Gobeil et al 2005;Schoonover et al 2005;Lewis et al 2007;Girija et al 2007;Hur et al 2007;Shiddamallayya and Pratima 2008;Suthar et al 2010;Maani-Messai et al 2010), as well as self-purification of the streams (Heidenwag et al 2001;Vagnetti et al 2003;Cukrov et al 2008;Wei et al 2009;Vaikasas and Dumbrauskas 2010).…”
Section: Introductionmentioning
confidence: 99%